Ketonemia variability through menstrual cycle in patients undergoing classic ketogenic diet - Pasca, Ludovica; Ferraris, Cinzia; Guglielmetti, Monica; Varesio, Costanza; Totaro, Martina; Trentani, Claudia; Marazzi, Claudia; Brambilla, Ilaria; Ballante, Elena; Armeno, Marisa; Valenzuela, Gabriela Reyes; Caraballo, Roberto H.; et al. (Frontiers in Nutrition, 2023)
Introduction Ketogenic dietary therapies (KDT) are well-established, safe, non-pharmacologic treatments used for children and adults with drug-resistant epilepsy and other neurological disorders. Ketone bodies (KBs) levels are recognized as helpful to check compliance to the KDT and to attempt titration of the diet according to the individualized needs. KBs might undergo inter-individual and intra-individual variability and can be affected by several factors. Possible variations in glycemia and ketone bodies blood levels according to the menstrual cycle have not been systematically assessed yet, but this time window deserves special attention because of hormonal and metabolic related changes. Methods This study aims at searching for subtle changes in KBs blood level during menstrual cycle in female patients undergoing a stable ketogenic diet, by analyzing 3-months daily measurement of ketone bodies blood levels and glucose blood levels throughout the menstrual cycle. Results We report the preliminary results on six female patients affected by GLUT1DS or drug resistant epilepsy, undergoing a stable classic ketogenic diet. A significant increase in glucose blood levels during menstruation was found in the entire cohort. As far as the ketone bodies blood levels, an inversely proportional trend compared to glycemia was noted. Conclusion Exploring whether ketonemia variations might occur according to the menstrual cycle is relevant to determine the feasibility of transient preventive diet adjustments to assure a continuative treatment efficacy and to enhance dietary behavior support. Clinical trial registration clinicaltrials.gov, identifier NCT05234411.